Brief Review of Newer Antiglycemic Agents as Options in the Treatment of Diabetic Kidney Disease - Brian K Irons; Molly Minze; Lisa Chastain; Michael E McMurry (Global Journal of Obesity, Diabetes and Metabolic Syndrome - Peertechz Publications, 2020)
Diabetes remains the leading cause of chronic kidney disease and with its increased prevalence the risk for Diabetic Kidney Disease (DKD) continues to rise and has a significant impact on diabetes morbidity and mortality as well as health care resources. There is a clear need to clinicians and patients for new treatments to limit the burden of DKD. Three classes of non-insulin therapy for type 2 diabetes mellitus (T2DM), dipeptidyl peptidase 4 (DPP4) inhibitors, glucagon-like peptide 1 (GLP1) agonists, and sodium glucose co-transporter 2 (SGLT2) inhibitors have been evaluated in large cardiovascular safety studies in which exploratory or post-hoc analyses shed some light on renal outcomes with these agents. Smaller studies focused on efficacy and safety in patients with T2DM and diabetic kidney disease also provide some evidence of renal outcomes. As a class, both DPP4 inhibitors and GLP1 agonists show promise in reducing albuminuria but have so far not been shown to impact more robust renal outcomes such as doubling of serum creatinine or progression in renal insufficiency. More compelling data exist on the benefits of SGLT2 inhibitors. From the cardiovascular safety studies, empagliflozin, canagliflozin, and dapagliflozin have shown reductions in not just albuminuria, but also show significant reductions in progression of renal insufficiency and a small reduction in the development of end-stage renal disease. The cardiovascular safety studies, however, were not designed to specifically assess renal benefit. Canagliflozin in a landmark trial specifically designed to evaluate its use in patients with diabetes and DKD, has shown to reduce doubling of serum creatinine, progression to end-stage renal disease while also demonstrating a reduction in cardiovascular morbidity as well. It is the first agent in nearly twenty years to obtain an indication for the treatment of DKD.